Bed-load through emergent vegetation. (July 2019) - Armanini, Aronne; Cavedon, Valentina
Highlights: Bed-load capacity through emerging vegetation depends on two dimensionless parameters only: modified dimensionless bed load and modified flow intensity parameter. The above two parameters are modified to account for vegetation density, the relative size of vegetation and the dimensionless diameter. The new general formulation is valid with and without of vegetation. Abstract: The paper deals with bed-load rates in a mobile bed channel with emerging vegetation. We have adapted the probabilistic/deterministic sediment transport model of Armanini et al.(2015) to account for changes in the flow field induced by vegetation. In addition to the two dimensionless parameters proposed by Einstein(1950), Φ and Ψ, the new adapted model also depends on a third dimensionless parameter representative of vegetation size and density. The adaptation requires two major changes to the original model byArmanini et al. (2015) . Firstly, the presence of vegetation reduces the bed area that is active with processes of sediment entrainment and deposition. To account for this, we propose reducing the net unit area useful for the exchange of sediments between bed and flow in proportion to vegetation density. This hypothesis implies redefining Einstein's parameter Φ, which represents the dimensionless sediment transport rate. Secondly, the presence of vegetation modifies some important parameters that, according to the adopted model, contribute to the formation of the bed load, (i.e. probability distributions of the particle hop length and detachment). Instead of adapting the bed-load formula to account for vegetation, we propose redefining both of Einstein's dimensionless parameters, Φ and Ψ, so that they are functions of the vegetation characteristics. This formulation is compared with a wide range of experimental data obtained in a laboratory channel, where the plants were represented by rigid emerging cylinders of different sizes and distribution densities within the channel. Under statistically homogenous and stationary conditions, these tests provided solid flow rates and hydrodynamic characteristics for 93 configurations with different values of hydrodynamic, granulometric and stem parameters. The comparison between experimental results and theoretical predictions shows the validity of the approach.